2022
DOI: 10.3389/fped.2022.958658
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe COVID-19 in people with cystic fibrosis: A systematic review

Abstract: BackgroundPeople with cystic fibrosis (CF) are considered a clinically fragile population with an intrinsic higher risk of developing severe COVID-19, though a certain variability in terms of outcomes and hospitalization has been noticed.AimTo highlight the main risk factors for severe COVID-19 in patients with CF.MethodsA systematic review of the current literature was conducted through PubMed and EMBASE databases. English-written articles reporting clinical data on CF subjects with SARS-CoV2 infection were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…Here, it was found that many cystic fibrosis patients had mild disease and common risk factors such as diabetes and previous solid organ transplantation, but subgroups of patients exhibited increased hospitalization rates and younger age at presentation relative to the general population. 117
Fig 1 Features of cohorts of patients with IEI and SARS-CoV-2 infection. (A) Age of patients with the indicated IEI.
…”
Section: Sars-cov-2 Infection Covid-19 and Ieimentioning
confidence: 99%
“…Here, it was found that many cystic fibrosis patients had mild disease and common risk factors such as diabetes and previous solid organ transplantation, but subgroups of patients exhibited increased hospitalization rates and younger age at presentation relative to the general population. 117
Fig 1 Features of cohorts of patients with IEI and SARS-CoV-2 infection. (A) Age of patients with the indicated IEI.
…”
Section: Sars-cov-2 Infection Covid-19 and Ieimentioning
confidence: 99%
“…A systematic review of the risk factors for severe COVID-19 disease in pwCF [1] identified the main risk factors for hospitalization included percent predicted forced expiratory volume in 1 second (ppFEV 1 ) <70, CF-related diabetes (CF-RD), age >40 years, pancreatic insufficiency, lower body mass index (BMI) and previous lung transplant. In the pediatric CF population lung function and BMI Z-score were both found to be significantly lower in hospitalized children, compared to non-hospitalized ones.…”
Section: Covid-19mentioning
confidence: 99%
“…Data from the European Cystic Fibrosis Patient Registry showed that general symptoms were the most common in the context of a COVID-19 infection, including fever, fatigue, myalgia/arthralgia and headache, followed by increased cough and pulmonary exacerbation [ 8 ]. However, transplant status was still considered one of the main risk factors for serious outcomes and these patients were therefore given priority in the vaccination program [ 9 ]. In view of the rapid spread of the infection, vaccines were developed very quickly.…”
Section: Introductionmentioning
confidence: 99%